Institutional Management of Villageowned Enterprises (BUMKAM) in Maredan Barat Village, Tualang District Siak Regency - Dafetta Fitri Linda; Wilson Wilson; Muhammad Jais; Ijayani Ijayani (Universitas Negeri Padang, 2023)
The Village-Owned Enterprise (BUMKam) is a business institution located in a village or rural area, which aims to increase income and strengthen the local economy. The effectiveness and efficiency of the BUMKam program in achieving its objectives depend on good management in its implementation. This study aims to examine the institutional management of BUMKam in Kampung Maredan Barat, Tualang District, Siak Regency. A qualitative descriptive approach was used in this study, and primary data were obtained through interviews and observations of key informants, namely the Director of BUMKam, the Treasurer of BUMKam, and the Head of Kampung Maredan Barat. The results of the study show that BUMKam Maredan Barat has good management, which is evidenced by (1) planning, including socialization to the community, the recruitment system for members being in line with the BUMKam standard operating procedures, and the implementation of three flagship programs, namely the savings and loan unit, agricultural unit, and development unit; (2) organizing, which involves assigning tasks to BUMKam employees in accordance with their designated positions; and (3) monitoring and evaluation, which are carried out by the Head of Kampung Maredan Barat and relevant agencies annually, and providing training or workshops to improve the skills of BUMKam employees in managing the institution.